Time and income poverty: an interdependent multidimensional poverty approach with German time use diary data - Society for the Study of Economic Inequality, Palma de Mallorca; Merz, Joachim; Rathjen, Tim (Palma de Mallorca, 2009)
"Income as the traditional one dimensional measure in well-being and poverty analyses is extended in recent studies by a multidimensional poverty concept, however, two important aspects are missing: time as an important dimension and the interdependence of the often only separately counted multiple poverty dimensions. Our paper will contribute to both aspects: We consider time – and income – both as important resources of everyday activities; the interdependence of the poverty dimensions will be evaluated by the German population. Referring to the time dimension, we follow Sen’s capability approach and argue, that restricted genuine, leisure time might exclude from social participation. The substitution between income and genuine leisure time is estimated by a CES-utility function of general utility with the German Socio-Economic Panel. We disentangle time, income and interdependent multidimensional poverty regimes characterising the working poor by a multinomial logit based on German 2001/02 time use diary data. One striking result: the substitution between time and income is significant and we find an important fraction of time poor who are unable to substitute their time deficit by income. These poor people are ignored within the poverty and well-being as well as the time crunch/time famine discussion so far."